Fault Identification Using Satellite Imagery, Gravity, and Seismicity Data on Lombok Island - Muhammad Aryanto; Ira Mutiara Anjasmara; Putra Maulida (Postgraduate, University of Mataram, 2025)
Lombok Island has a high level of earthquake vulnerability due to local tectonic activities. Although most earthquakes on land have small magnitudes (M < 5), their proximity to settlements has the potential to cause significant impacts. This study aims to identify the potential for active faults using a multi-data approach, specifically utilizing gravity anomaly data from GGMplus. In addition, Sentinel-1 data is used for surface lineament extraction and DEMNAS for topography. Analysis of gravity data utilizing GGMPlus reveals that the Batujahe Fault exhibits thrust faulting characteristics, whereas the South Lombok Fault displays normal faulting behavior. Automated lineament extraction yielded a total of 54 surface structural lineaments within the study area, spanning a cumulative length of 478 km. These results provide a shorter fault length than the existing fault map. Statistical analysis of the extracted lineaments revealed three dominant trends: N-S, NE-SW, and NW-SE, with the N-S trend being the most predominant. Notably, these findings diverge from prior studies, which classified the Batujahe Fault as a strike-slip fault and the South Lombok Fault as a thrust fault, underscoring the complexities of fault dynamics in the region, however derivative methods fail to detect the Alas Strait strike-slip fault.